Model Komunikasi Advokasi Pencegahan Korupsi Pada Media Publikasi Humas Lembaga KPK - Jhanattan, Mohammad (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2020)
The communication strategy implemented by the KPK is to accurately and systematically usethe media as a conveyor of advocacy. The partnership built by the KPK Public Relations team withthe media crew is by giving official press releases. The excerpts from the press release come fromelements of the Leadership, Spokesperson, Structural Officials, Advisors, and Prominence Person.Advocacy carried out through the media includes introducing KPK work programs, Anti-CorruptionEducation, Research and Development Study Results Reports (R & D), determining the status ofsuspects at press conferences and / or delivering the results of a sting operation. Especially for mediathat is managed independently by the KPK, through online services (live streaming) it hasspecificities, among others, to deliver news about the prosecution and prevention of corruption,discussion of anti-corruption law (Legal Clinic), educational shows for families and children, as wellas contemporary content that contains things that are closely related to people's daily lives. Thisform of live streaming can be re-recorded as Pod Cast (video recording on demand). In terms of thedelivery technique as well as the content of the program, the responsibility for the content andcopyright is fully owned by the KPK.